2+-6m=-4m+10

Simple and best practice solution for 2+-6m=-4m+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+-6m=-4m+10 equation:


Simplifying
2 + -6m = -4m + 10

Reorder the terms:
2 + -6m = 10 + -4m

Solving
2 + -6m = 10 + -4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '4m' to each side of the equation.
2 + -6m + 4m = 10 + -4m + 4m

Combine like terms: -6m + 4m = -2m
2 + -2m = 10 + -4m + 4m

Combine like terms: -4m + 4m = 0
2 + -2m = 10 + 0
2 + -2m = 10

Add '-2' to each side of the equation.
2 + -2 + -2m = 10 + -2

Combine like terms: 2 + -2 = 0
0 + -2m = 10 + -2
-2m = 10 + -2

Combine like terms: 10 + -2 = 8
-2m = 8

Divide each side by '-2'.
m = -4

Simplifying
m = -4

See similar equations:

| -9(y-1)=2-8y | | -3x(x+5)-7=-8+10 | | 3a-(5-3a)=10 | | 4(q)+(-1)(1-q)=1q+2(1-q) | | 5x+-6=3x+-8 | | (3-x)+(x-4)=2(x+4) | | w=-125t+6000 | | -6+5(-9x-3)=-10 | | -6+(-9x-3)=-10 | | 24+r=28 | | 5p+8=-32 | | 2=-19+z | | 6m-4=4m | | 2=-4+k | | 18p^3-63p^2-9p=0 | | 4x^2+8x+48y-44=0 | | -7(2x-8)+3=-14x+59 | | 10-4=16 | | Q-3=25 | | F(x)=ln(x)*x^2 | | 66=10-8b | | K-12=11 | | b/2=-7 | | 4b+3a= | | 1-2r=9-r | | 12x^4-26x^3+10x^2=0 | | 9x-2=9(x+8) | | 8=6-p(p+3) | | 2x(6x^3-13x^2+5x)=0 | | 8y^3+6y^2-9y= | | 5(32n-40)=4(5n+1) | | x=2(1-x) |

Equations solver categories